(untitled) (International Journal of Physiotherapy, 2025)
Background: Genu recurvatum (GR) is characterized by hyperextension of the knee or back knee. It leads to retardation in the strength and balance of the quadriceps. Optimal muscular strength and balance are required for performing daily activities. Articles concentrate on the strength of the quadriceps and balance in GR. Still, negligible studies have been working towards isolating the correlation between the strength of quadriceps muscles and balance in GR versus individuals without GR. The present study aimed to find a correlation between strength and balance of quadriceps between healthy individuals versus individuals with GR. Methods: A cross-sectional study comprising 64 patients, 30 regular and 30 with GR were enrolled. An isokinetic dynamometer was used to assess quadriceps strength, and the Y Balance lower quarter test (YB-LQT) was used to assess balance in healthy individuals and individuals with GR. Results: Peak knee extension torque (PKET) generated from the right limb is found to be moderately correlated to the performance of the composite score of YB-LQT in individuals with GR (r=0.48; r=0.44). In contrast, PKET is weekly correlated with the performance of the composite score of YB-LQT for healthy individuals (r=0.028; r=0.163). When comparing both groups, no significant difference was found between them. Conclusion: While each test measures a unique construct, there is an association between its components. In individuals with GR, YB-LQT, and isokinetic strength tests find asymmetries and propose using them as outcome measures before and after therapeutic interventions.